Could Sumac Be Effective on COVID-19 Treatment? - Korkmaz, Hasan (Mary Ann Liebert, Inc, 2021)
Sumac is an herbal product, commonly consumed as a spice and was used for medical treatment for centuries. The phytochemical structure of Sumac was studied extensively, and it was established that the herb contained tannins, polyphenols, flavonoids, organic acids, and essential oils. Various scientific studies demonstrated that Sumac had a free oxygen radical-scavenging effect, a protective effect against liver damage, antihemolytic, leukopenia, and antifibrogenic effects, along with its antiviral, antimicrobial, anti-inflammatory, and antioxidant properties. Recently, several scientific studies described the pathophysiology, clinical course, and the treatment of COVID-19 infection. The examination of the characteristics of COVID-19 infection revealed via the clinical studies suggests that Sumac extract could be useful in the treatment of COVID-19. Given the scientific studies focusing on the beneficial effects of Sumac, the present review aims to provide an encouraging viewpoint to investigate whether Sumac is effective in treating COVID-19 infection.
Keywords: antiviral; COVID-19; extract; Sumac